Bismuth(V) mediated meta-arylation - Senior, Aaron James (2022)
Despite offering many options for functionalisation, unattractive synthetic routes have left 2,4-cyclohexadienones relatively unexplored. Reported methods to make these substrates are marred by poor regio- and chemoselectivity, toxic reagents, and inefficient processes. The work detailed in this thesis aims to remove barriers to implementation by presenting a synthetic method for their preparation that is selective and predictive, uses benign reagents, and offers excellent yields. To showcase their applicability in synthetic organic chemistry, they will be used as intermediates in the synthesis of meta-substituted phenols and anilines.